Rwanda: Rebuilding of a Nation - Nkusi, A.; Rwagatare, Joseph; Ndahiro, Alfred (Book collections on Project MUSE., 2015)
A story that takes the reader through a sweeping panorama of Rwanda's history, from its recent past as a near-failed state to its present as a beacon of hope and successful innovations. Rwanda's rise from ashes detailed in this book is the culmination of a visionary and laborious process of rebuilding a nation from the brink of collapse. It is also a story of reconciling a people that had been taught to see each other as enemies.